Risk Factors of New Cerebral Infarctions After Endovascular Treatment for Basilar Artery Stenosis Based on High-Resolution Magnetic Resonance Imaging - Luo, Jichang; Li, Long; Wang, Tao; Yang, Kun; Feng, Yao; Yang, Renjie; Ma, Yan; Gao, Peng; Yang, Bin; Jiao, Liqun (Frontiers in Neurology, 2021)
Objective: The current study aims to analyze the risk factors of new cerebral infarctions detected by diffusion-weighted imaging (DWI) after endovascular treatment in patients with severe basilar artery stenosis. Methods: Data was collected from the electronic medical records of patients with severely atherosclerotic basilar artery stenosis (≥ 70%) who underwent endovascular treatment. The plaque characteristics, including the plaque distribution, plaque burden, plaque enhancement index, remodeling ratio, and stenosis degree, were evaluated qualitatively and quantitatively using high-resolution magnetic resonance imaging (HR-MRI) and digital subtraction angiography (DSA). The characteristics of the procedure, such as the type of treatment, balloon diameter, balloon length, stent diameter, and stent length, were analyzed. Results: A total of 107 patients with severe basilar artery stenosis (≥ 70%) who underwent endovascular treatment were enrolled. The study participants included 77 men and 30 women, with an average age of 61.6 ± 8.1 years. The rate of postoperative new cerebral infarctions was 55.1% (59/107), of which 74.6% (44/59) were caused by artery-to-artery embolism, 6.8% (4/59) due to perforator occlusion, and 18.6% (11/59) were caused by a mixed mechanism. Twelve of 59 patients had ischemic events, with nine cases of stroke and three cases of transient ischemic attacks (TIA). The plaque burden in the DWI-positive group was significantly larger than that in the DWI-negative group (3.7% vs. -8.5%, p = 0.016). Positive remodeling was more common in the DWI-positive group than in the DWI-negative group (35.6% vs. 16.7%, p = 0.028). Smoking was inversely correlated with the rate of new cerebral infarctions (odds ratio, 0.394; 95% confidence interval, 0.167–0.926; p = 0.033). Conclusion: The plaque characteristics are not associated with new cerebral infarction, although the large plaque burden and positive remodeling are more likely to appear in patients with new cerebral infarctions after BA stenting, which warrants further studies with large sample size. As for smoking, the inverse correlation with new cerebral infarctions needs large-scale prospective randomized controlled trials to verify.